Soil quality response to organic amendments on dryland red soil in subtropical China - Li, Peng; Wu, Mengcheng; Kang, Guodong; Zhu, Baijing; Li, Huixin; Hu, Feng; Jiao, Jiaguo (Geoderma, 2020)
•Organic input can improve soil quality by the interaction of soil properties.•Use animal-derived organic fertilizer had better soil quality than plant-derived.•AP, AN, GP and AK were selected as a minimum data set for evaluating soil quality.•Information from soil indicators is integrated into a standardization framework.•Appropriate methods of scoring and weighting are determined in the framework. Organic fertilizer applications can increase soil fertility and productivity and reduce chemical fertilizer use. However, few experimental studies have focused on effects of organic fertilizers on soil quality in a field ecosystem. The overarching goal of this study was to develop a soil quality index (SQI) for fertilization management in red soil farmland in China. The specific objectives were to determine 1) appropriate soil quality indicators, 2) a suitable weight assignment method (PCA, principal component analysis or MRA, multiple regression analysis) and 3) the optimal scoring function (standard or linear or non-linear). We analyzed 40 soil physical, chemical, biochemical and biological properties under nine fertilization treatments (CK (no fertilizer), CF (chemical fertilizer), RF (60% chemical fertilizer), CFS (chemical fertilizer + straw), RFS (60% chemical fertilizer + straw), CFB (chemical fertilizer + biochar), RFB (60% chemical fertilizer + biochar), RFP (60% chemical fertilizer + pig manure), RFV (60% chemical fertilizer + vermicompost)) as potential soil quality indicators. Principal component analysis and correlation analysis were applied to determine the indicators responsive to management and for the confirmation of the six SQIs. Available phosphorous, nitrogen, potassium and gram-positive bacteria were chosen as the minimum data set from the total of 40 soil indictors. Management of organic and inorganic fertilizers affected each soil property in different ways, and the index based on the minimum data set, calculated using standard scoring function and weight assignment method of multiple regression analysis, was most accurate and sensitive. Application of a pig manure or vermicompost significantly increased SQI values relative to other treatments, followed by straw or biochar treatments which were higher than a single application of chemical fertilizer. These results indicate that the addition of organic fertilizers will not only improve soil quality, but also enhance rapeseed and sweet potato yield compared to chemical fertilizers. Additionally, the SQI method can provide a practical and quantitative tool for the evaluation of soil quality.